THE IMPACT OF PUBLIC CONSORTIUM IN ENVIRONMENTAL SPENDING FROM MUNICIPALITIES IN SOUTHERN BRAZIL - Broietti, Cleber [UNESP]; Souza, João Antônio Salvador De; Flach, Leonardo; Silva, Gilberto Crispim; Ferreira, Celma Duque (ANPPAS - Revista Ambiente e Sociedade, 2020)
Environmental preservation is a State responsibility, and the State use public resources. Control and understand how and what impact the environmental spending is important to check the performance and concerns of public managers with the environment. This study aims to determine the influence of the participation of environmental public consortium located in the south of Brazil in environmental expenditures of the municipalities between 2012 and 2016. The research method is based on a multivariate model with pooled data, applying Pooled Ordinary Least Squares. The results show that in this region there twenty consortium, made up of 308 municipalities. It was found that the consortium have positive and statistically significant influence on environmental spending.

La preservación ambiental es responsabilidad del Estado, y éste se utiliza de recursos públicos para hacerlo. Controlar y entender cómo y qué impacta el gasto ambiental es importante para verificar el desempeño y la preocupación de los gestores públicos con el medio ambiente. Este estudio buscó verificar la influencia de la participación de los consorcios públicos ambientales ubicados en el sur de Brasil en los gastos ambientales de los municipios entre 2012 y 2016. El método de investigación se basa en un modelo multivariado con datos apilados por la técnica agrupada OLS. Los resultados apuntan que hay en esa región veinte consorcios, constituidos por 308 municipios. Se verificó que los consorcios presentan una influencia positiva y estadísticamente significativa en los gastos ambientales. Así, el estudio contribuye a constatar que las relaciones interorganizacionales influyen en los gastos ambientales.
EL IMPACTO DE LOS CONSORCIOS PÚBLICOS EN EL GASTO AMBIENTAL EN LOS MUNICIPIOS DEL SUR DE BRASIL
Keywords: public consortium; environmental expenditure; Southern Brazil